Amniotic Membranes - A Futuristic Trend in Periodontal Regeneration - KAREEM, NASHRA (The journal of contemporary issues in business and government, 2020)
One of the most frequent indications of periodontal plastic surgery is the treatment of gingival recessions. This treatment has mainly been justified by the patient’s wish to improve the aesthetic appearance when there is an exposed root. The ultimate goal of a root coverage procedure is complete coverage of the recession defect with a good aesthetic appearance related to the adjacent soft tissues, minimal probing depth following healing and minimal postoperative discomfort. The selection of one surgical technique over another with the use of particular grafts depends on several factors to achieve optimal regeneration of the lost periodontal tissues via guided tissue regeneration (GTR). Over the years, various materials have been used as physical barriers in GTR. One such novel material that has been tried relatively recently is the amniotic or the placental membrane. The placental allografts possess various properties that may be beneficial as a barrier membrane in periodontal therapy. Therefore, this review article elaborately explains the basic features, actions and applications of amniotic membranes that can be used as a remarkable tool in the field of periodontal regeneration.